2019
DOI: 10.1002/ejoc.201900725
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalysed C–C Bond Formation and [2+2+2] Annulation of 1,3‐Dicarbonyls to Terminal Alkynes

Abstract: A highly regioselective [Cp*Co(CO)I2]‐catalyzed addition of 1,3‐diketones to terminal alkynes at room temperature has been achieved using Cu(OTf)2 as a co‐catalyst. The reaction of 1,3‐diketones substituted at active methylene carbon with phenyl acetylenes having an electron‐withdrawing group or a bulky group results in the formation of the 2‐alkenylated 1,3‐dicarbonyl product, but phenyl acetylenes with electron donating group led to the formation of tetrahydronaphthalene and terphenyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In 2003, Nakamura et al documented an indium-catalyzed addition of 1,3-dicarbonyl compounds to unactivated 1-alkynes 23 , providing an efficient synthetic route to form 2-alkenyl-1,3-dicarbonyl compounds from abundant carbon alkynes sources. After that, In(III) 24 28 , Re(I) 29 31 , Ir(I) 32 , Pd(0) 33 , Co(II) 34 , Mn(I) 35 , 36 , and Ru(I)-(III) 37 39 catalytic systems were discovered, all of which were racemic reports except for only one example using substrates with chiral auxiliary 40 . All the above reports, the dicarbonyl compounds and alkynes need to be activated simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Nakamura et al documented an indium-catalyzed addition of 1,3-dicarbonyl compounds to unactivated 1-alkynes 23 , providing an efficient synthetic route to form 2-alkenyl-1,3-dicarbonyl compounds from abundant carbon alkynes sources. After that, In(III) 24 28 , Re(I) 29 31 , Ir(I) 32 , Pd(0) 33 , Co(II) 34 , Mn(I) 35 , 36 , and Ru(I)-(III) 37 39 catalytic systems were discovered, all of which were racemic reports except for only one example using substrates with chiral auxiliary 40 . All the above reports, the dicarbonyl compounds and alkynes need to be activated simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…7 Another report deals with Ir(I) catalysed Nakamura reaction. 8 Kuninobu et al reported that [Re(CO) 3 -Br(THF)] (3 mol%) catalyses the Nakamura reaction at 50 C. 9 It may be noted that to the best of our knowledge to date Nakamura reaction catalysed by an earth abundant rst-row transition element has not been reported except a couple of reports, one on Mn(CO) 5 Br (5 mol%) 10 and another on Cp*Co(CO)I 2 (5 mol%) + Cu(OTf) 2 (5 mol%) 11 catalysed addition of dicarbonyl compounds to alkynes and (2 + 2 + 2) cycloaddition. All these methods either suffer from very harsh reaction conditions or require expensive ligands or expensive additives.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Nakamura and co-workers documented an indiumcatalyzed addition of 1,3-dicarbonyl compounds to unactivated 1-alkynes 23 , providing an e cient synthetic route to form 2-alkenyl-1,3-dicarbonyl compounds from abundant carbon alkynes sources. After that, In(III) [24][25][26][27][28] , Re(I) [29][30][31] , Ir(I) 32 , Pd(0) 33 , Co(II) 34 , Mn(I) [35][36] , Ru(I)-(III) 37-39 catalytic systems were discovered, all of which were racemic reports except only one example using substrates with chiral auxiliary 40 . All the above reports, the dicarbonyl compounds and alkynes need to be activated simultaneously.…”
Section: Introductionmentioning
confidence: 99%